Does Digital Marketing Effect Grabfood Purchase Desicision - Devy Widya Apriandi; Ananda Periana (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2023)
Every company must be able to survive and compete in its industry. Understanding consumer desires and being able to influence consumer purchasing decisions can support companies to survive and compete in their competition. The rapid development of information and communication technology encourages business people to develop their businesses, by continuing to innovate. Likewise with Grab with the presence of GrabFood. This research was conducted to see the importance of the relationship between digital marketing and consumer purchasing decisions in the Grab application, but on the other hand, Grabfood has weaknesses in digital marketing, so improvements need to be made to strengthen consumer purchasing decisions. This research was carried out on Stiesa and UIS students, the research method used was a quantitative approach with a verification type of research, with a data collection technique, namely a questionnaire with 60 respondents. A simple linear regression analysis tool, hypothesis testing is carried out using the T test. The research results show that digital marketing simultaneously has a significant effect on consumer purchasing decisions.